Democratic legitimacy in the post-crisis EMU. Issue 3 (2nd April 2020) - Crum, Ben; Merlo, Stefano
ABSTRACT: This paper examines the democratic legitimacy of Economic and Monetary Union (EMU) since the international financial crisis hit the euro area. From its inception, EMU has been marked by an asymmetry as its monetary pillar relied on output legitimacy while its economic pillar relied essentially on input legitimacy at the national level. The crisis severely challenged EMU's output legitimacy, which led to the establishment of new European-level institutions. We analyse the European Stability Mechanism, the European Semester, and Banking Union to take stock of their powers and the ways that these are balanced by mechanisms of legitimacy. Our main finding is that the intergovernmental and output-oriented approach that originally informed the legitimacy of EMU has remained prevalent after the crisis. However, as the three domains – in varying degrees – address questions that are essentially political, we argue that the channels for input legitimacy at the European level remain deficient.